Perancangan Kampanye Pentingnya Air Mineral Terhadap Karyawan Kantor Berusia Muda Di Jakarta Dalam Bentuk Animasi - Kamarga, Hansen; Septian Rachman, Vicky (BHAGIRUPA, 2022)
Humans need to eat and drink as a source of energy for survival, about 70% of the parts in the human body are in the form of liquid, and human organs really need fluids to work. The human body requires 230 ml of water per day or a total of 2 liters. The types of water are divided into 3, the first is mineral water, demineralized water, and alkaline water. Unfortunately, there are still many office workers in Jakarta who don't really care about the importance of maintaining health by drinking mineral water. There are quite a number of negative impacts caused by not drinking enough mineral water, but they are ignored, or underestimated.